Process optimization studies on xylanase production and bioethanol fermentation - Chia Zhi Tan; Thien Sze Chen Ivory; Yi Peng Teoh; Kok Chang Lee; Balakrishnan Kunasundari; Xian Ooi Zhong (E3S Web of Conferences, 2025)
Xylanase is one of the hydrolytic enzymes with a broad industrial application in several industries. Bioethanol can be synthesised from lignocellulosic biomass by using xylanase and other hydrolytic enzymes. A filamentous fungus, which is Aspergillus niger produces xylanase under submerged fermentation when oil palm empty fruit brunches were used as carbon sources. This study aimed to optimize the operating conditions (medium pH and incubation temperature) of xylanase production process using the OFAT analysis technique. From the data obtained, the highest xylanase production was 0.508 U/mL at pH 5.0 and 0.524 U/mL at an incubation temperature of 32°C, respectively. S. cerevisiae yeast was added into the fermentation supernatant for bioethanol fermentation. The concentration of bioethanol produced by xylanase enzyme from A. niger at optimum operating condition was 15.54±0.47 g/L. This study proved that A. niger is one of the filamentous fungi which show the potential of hydrolysing lignocellulosic material to carbon sources and subsequently to bioethanol production.